EVALUASI DAN REMIDIASI DALAM PEMBELAJARAN BAHASA DAN SASTRA MULTILITERASI - Fadli, Rusli Ilham (Discovery, 2018)
ABSTRAK Multiliteration is currently a learning method that has been developed by teachers, who previously used literacy that only read and write less widely, currently multiliteration of students can develop ways of reading and using various internet media and free media. Multiliteration remains to read and write. In reading students must have a septetap concept to read and write. In reading students must have a septetap concept to read and write. In reading students must have criteria such as characters, taste, creativity, and desire, which allows each reader. Indonesian language learning has a very important role not only for communication and also for the benefit of mastering science. According to Ghazali (2010: 168) language learning is "a process that runs linearly, which starts with English (listening and speaking) and then switches to written language (reading and writing). So, nothing is interconnected and cannot be used in the learning process. However, reading and writing are very important, this is caused by reading for tools for things that can increase knowledge and the development of messages in young reading material can be written in writing, namely writing. Even so, reading and writing books are easy to do and learn through the right learning process. The ability to read and the ability to write relationships that cannot be ignored. Based on the photoshoot about learning to read and write above the Target. The evaluation results of Bloom's Taxonomy include cognitive, affective, psychomotor domains. In the third 2013 curriculum, it is used in research, so researchers will share it and provide remediation solutions. Evaluation of learning has two dimensions, namely the evaluation of the learning process and evaluation of learning outcomes. Evaluation of the learning process is an evaluation system that needs to be done by the teacher to determine the quality of learning. this activity is referred to as a reflection of the learning process with this activity the teacher can find the advantages and disadvantages of the learning process that has been done. Evaluation of the learning process is a process to determine the value, services or benefits of learning activities through assessment and measurement activities. Making learning evaluations includes consideration of results, services, learning processes, and program benefits (Dimyati and Mudjiono, 2006: 221). Evaluation of learning outcomes emphasizes the information to what extent the results of the evaluation achieved by students in accordance with the stated goals. Thus, evaluation of learning outcomes sets the good and bad results of learning activities. Researchers in determining the results of evaluation in learning multiliteration language and literature divide it into three domains that each of them has its own evaluation method. The 2013 curriculum system requires teachers that every basic competency can be evaluated so that students will achieve completeness in every competency. A separate evaluation system has an impact on the instructor as, the instructor must combine the way of learning, the teacher seeks material that matches the combination of three competencies. Multiliteration evaluation allows the teacher to work hard to find reading material and learning models that can exclude the three competencies. Reading and writing have separate assessment criteria.